Laser-Induced Breakdown Spectroscopy Applied on Liquid Films: Effects of the Sample Thickness and the Laser Energy on the Signal Intensity and Stability - Lazic, Violeta; Ciaffi, Massimiliano (Journal of Spectroscopy, 2017)
Droplets of organic liquids on aluminum substrate were probed by an Nd:YAG laser, both in a steady state and during rotation at speeds 18–150 rpm. Rotation transforms the droplet into film, which estimated thickness at high speeds was below 3 μm and 20 μm for diesel and peanut oil, respectively. Line intensities from the liquid (C I) and the support (Al I) material were tracked as a function of the film thickness and the laser energy. By film thinning, the line intensities from liquid sample were enhanced up to a factor 100x; simultaneously, the LIBS signal fluctuations were reduced 5–10 times with respect to the steady droplet. In certain experimental conditions, the line intensities from the support material become very weak with respect to the C I line, indicating an efficient screening of the substrate by highly excited plasma from the liquid layer. At a fixed rotation speed, there is a laser energy threshold, dependent on the liquid thickness, above which the LIBS signal becomes stable. Here, we discuss the relative processes and optimization of the experimental conditions for the LIBS measurements frome one laser shot to another.